Mitogenomic characterization and phylogeny of Scelimena melli Günther (Orthoptera: Tetrigoidea: Scelimeninae). Issue 10 (3rd October 2021) - Li, Xuejuan; Lin, Chuhui; Wang, Lenan; Gao, Zichen; Zhu, Tingting; Lin, Liliang
Abstract: The mitochondrial genome (mitogenome) of Scelimena melli, which belongs to Orthoptera, Tetrigoidea, Tetrigidae, Scelimeninae was determined. The mitogenome has a length of 14, 598 bp and consists of 37 genes including 13 protein-coding genes (PCGs), two rRNA genes, and 22 tRNA genes. Phylogenetic analysis using 37 mitochondrial genes with other 22 Tetrigoidea species revealed that S. melli had a closer relationship with Paragavialidium sichuanense, but the monophyly of Scelimeninae was not recovered. The mitogenome data of S. melli would provide useful resources for further evolutionary studies of Scelimeninae and Tetrigoidea species.